Expanding APHON's Pediatric Chemotherapy/Biotherapy Provider and Instructor Program to Spanish-Speaking Countries: Pilot Series Development and Evaluation. (March 2023) - Sullivan, Courtney E.; Weber, Lorena Segovia; Lamas, Paola Viveros; Diaz, Dorian Navarro; Lu, Zhaohua; Zhao, Xiwen; Salinas-Avila, San Juanita; Ramos, Richard J.; Belderson, Kristin M.; Challinor, Julia
Background: To address the need for standardized, comprehensive chemotherapy/biotherapy education in Latin American and Caribbean (LAC) countries, the Association of Pediatric Hematology/Oncology Nurses (APHON) Pediatric Chemotherapy/Biotherapy Provider and Instructor program courses were culturally adapted, translated to Spanish, and piloted. The process of course adaptation and implementation are described. A Context, Input, Process, Product model outcomes evaluation determined: (a) differences in pass rates by test version and pilot location, (b) predictors of pass rates, (c) course appropriateness for nurses' education and practice levels, and (d) strategies for course improvements.Methods: The Spanish APHON Pediatric Chemotherapy/Biotherapy Provider program was piloted four times and the Instructor program twice with nurses from Mexico, Central America, the Caribbean, South America, and Spain. Statistical analysis identified factors associated with pass rates.Results: Of the 203 students in four Spanish APHON Provider program courses, data from 108 students (three pilots) were analyzed (one unplanned pilot excluded for missing data). Significant predictors of pass rates included: pediatric oncology frontline nurses ( OR = 9.86; 95% CI [2.56, 65.23]; p = .004), nurses dedicated to an inpatient or outpatient unit (non-rotating) ( OR = 6.79 [1.29, 51.98]; p = .033), and graduation from a 5-year nursing program ( OR = 5.92; 95% CI [1.30, 33.15]; p = .028).Discussion: The Spanish APHON Pediatric Chemotherapy/Biotherapy program was determined appropriate for nurses' education and practice levels in LAC countries. Through the APHON Spanish language instructor network, pediatric oncology nurses in LAC countries have increased access to standardized, comprehensive chemotherapy/biotherapy education.